Penguatan Usaha melalui Pelatihan Pembukuan dan Pemasaran Produk Ikan Asap di Desa Noelbaki Kabupaten Kupang - Marce Sherly Kase; Natalia Lily Babulu; Anggelina Delviana Klau (Politeknik Negeri Cilacap, 2022)
The topic of community service chosen by the community service team was sourced from initial observations made at the “Supel” Smoked Fish Home Industry (IRT) using local wisdom products from the East Nusa Tenggara (NTT) Province, namely Smoked Fish, so it needs to be preserved. This “Supel” Smoked Fish IRT will survive if it has good management in the form of financial management in accordance with accounting standards. Based on the Focus Group Discussion (FGD) conducted with IRT owners, it was found that the financial management of this IRT was not optimal, because while running the business, the